The relationship between Alvarado score and pain score in managing adult acute appendicitis in the Emergency Department - Ahmad KI,; Shamsul AS,; Ismail MS, (Department of Surgery, UKM Medical Centre, 2011)
Acute appendicitis is one of the most common differential diagnoses for acute abdominal pain made by emergency doctors. Suspected cases require surgical referral for observation or definitive intervention to prevent complications. A high index of suspicion and good clinical skills with the aid of scoring systems allows early decision making, which includes optimal pain control. The objective of this study was to identify the pain score and its relationship to the cut-off points of the Alvarado scoring system that justifies early surgical referral or discharge for suspected acute appendicitis from the emergency department. This was a cross sectional study of acute abdominal pain from June 2007 to September 2008. All patients who fulfilled the criteria and consented to the study were assessed for Alvarado score, verbal numerical pain score (VNRS) and their subsequent management. Patients with an Alvarado score of ≥7 were likely to have acute appendicitis (80.1% sensitivity and 52.63% specificity) and those with the score of ≤3 were unlikely to have acute appendicitis. The median pain score was 7.00 (IQR: 5.00-8.50) but 72.5% did not receive any analgesia. There was no direct relationship between pain score with Alvarado score. Oligoanalgesia in patients with acute appendicitis still exist in Emergency Department of UKMMC.